Establishing trust through home visits during pregnancy: a realist evaluation of a Danish breastfeeding support intervention - Anne Kristine Gadeberg; Ingrid Maria Susanne Nilsson; Ulla Christensen; Marie Honoré Jacobsen; Henriette Knold Rossau; Sarah Fredsted Villadsen (Archives of Public Health)
Abstract Background Breastfeeding has numerous health benefits but social inequality in breastfeeding is documented in many high-income countries. The evidence for improving breastfeeding support through prenatal encounters is conflicting, but points towards a mechanism activated through a positive relationship between the families and their health care providers. A Danish intervention included a home visit by a health visitor during pregnancy to prolong breastfeeding and reduce social inequality in its rates. The purpose of this study was to investigate how this home visit affected breastfeeding support across socioeconomic groups with attention to how, and for whom, it activated a mechanism of improved relationship and trust between the health visitor and the family. Methods Our study used a realist evaluation approach and was embedded in a cluster randomized trial carried out in 20 municipalities. In the intervention arm, we observed 35 home visits delivered by the health visitors, interviewed 16 mothers and conducted 6 focus groups with a total of 34 health visitors to examine the intervention mechanisms and contextual factors that influence the generation of outcomes. The analysis applied Luhmann’s, and Brown and Meyers’ concepts of trust as middle-range theories. Results The pregnancy home visit helped early establishment of trust which enhanced the subsequent breastfeeding support postpartum in numerous ways. In realist terms, our central mechanism of change, the establishment of trust, had optimal conditions for success in the contextual setting of the pregnancy home visit where there was time, peace, undisturbed conversations, mental capacity to reflection, and a perceived more even power balance between the family and the health visitor which resulted in a range of positive outcomes. The mechanism resulted in improved tailored breastfeeding support postpartum, families reaching out to the health visitor sooner when experiencing breastfeeding difficulties, and families expressing a more positive experience of breastfeeding. The mechanism was activated across the different socioeconomic groups. Conclusions The circumstances of the pregnancy home visit helped to establish trust between the health visitor and the family. Especially for families in vulnerable positions, the pregnancy home visit seems to be a potent driver for enhancing the gains from breastfeeding support.